Analysis of social inequalities in Peru. An introduction - Mejía Navarrete, Julio (2024)
The article presents an approach to the major trends of social inequality inPeru. Latin America is the most polarized region in the world. The country isimmersed in an intense process of reclassification of the population, beingconfigured with the ethnic-racial permanence imposed by the colony andthe disparities of neoliberal globalization, to reproduce an interdefined pat-tern of classes, racialization and gender that outline the greatest inequalitiesfrom the country.